An assessment of the provision of micro-credit for women empowerment in Plateau State, Nigeria - Lemut, Titus Isa (Penerbit Universiti Kebangsaan Malaysia, 2017)
The world has come to realize that micro-credit plays very important role in empowering women. Government, groups and individuals have established cooperative societies to pool resources together for the provision of microcredit to women. The study is concerned with the assessment of Country Women association of Nigeria (COWAN) in the provision of Micro-credit in Plateau State, Nigeria. The objectives of the study are to determine the demographic and socio-economic characteristics of the respondents, assess the role of COWAN in the provision of micro-credit, identify the sources of capital for their businesses and assess the impact of micro-credit on the respondents. A questionnaire was used for the collection of data while random sampling technique was used to select the samples. A sample size of 310 was adopted. The findings reveal that majority of the respondents have benefited from micro-credit. Some have received the loan once, twice, thrice, four times and some others many times. In the area of sources of capital to start small business the findings reveal that the sources include personal savings, government organizations, NGOs, husbands and from relatives and friends. This implies that the loans provided by NGOs and governments are not sufficient for small scale business of the COWAN respondents. The findings further reveal that majority of the respondents have experienced change of status in their socio-economic wellbeing as a result of the loans which they invested in their small scale business. Based on the findings of the research it is recommended that more NGOs should be established to provide loans to women for selfempowerment. Government should make policies that will sustain microfinance banks to provide one digit loans for women. Women should be encouraged to form cooperatives to pool resources together so that they can give loans to their members.